ANALISIS PROFIL ORGANISASI BELAJAR SEKOLAH TINGGI AGAMA ISLAM NEGERI (STAIN) PAREPARE - Muhammad Ahsan (Al-Ishlah: Jurnal Pendidikan Islam, 2016)
This study discusses the learning organization profile analyzes the STAIN Pare Pare. The method used in filling out this questionnaire is a self-evaluation method in which the institution or institutions assess themselves. The results of this study indicate that Subsystem Dynamics Learning: Individuals, groups or teams, and organizations, Organization Transformation Subsystem: Vision, Culture, Strategy and structure Subsystem: Human Resources Leader, Lecturer / Employee, Student, Partner, Supplier, and Society, Management Subsystem Knowledge: acquisition, creation, storage, retrieval, transfer, and utilization, and Subsystem Application Technology: Information Systems Science, Learning-Based technology and Electronic performance Support Systems fall into good category..